Potensi Ekstrak Kasar Teh Hitam (Camellia sinensis O.K. var. Assamica) sebagai Pewarna (Dye) pada Pembuatan Sela Surya Tersensitisasi (SSPT) - Deskawi, Oki; Ningsih, Rachmawati; Avisena, Novi; Hastuti, Erna (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2015)
Has done research on the manufacture of dye sensitized solar cells by utilizing the crude extract of black tea (Camellia sinensis var O.K. Assamica). This study aims to determine the potential of black tea extract as a dye in dye sensitized solar cell manufacturing. This study includes several stages: sample preparation of black tea, black tea sample extraction in a mixture of acetic acid: methanol: distilled water (4:25:21), analysis of the crude extract of black tea using UV-Vis, color density analysis using a color reader, testing DSSC obtained by measuring voltages and currents strong produced under conditions halogen lamp illuminated with a light intensity of 4.488 Watt/m2, the identification number of the crude extract of pigments by TLC analytical. The results of the characterization black tea extract is flavonoids. That it contains theaflavins shown with a maximum wavelength 273 nm. Color of black tea using a color reader testing showed reddish yellow (orange) with the color density reached 78,3%. Voltage maximum and maximum current strength produced by 107,3 mV and 2.13 x 10 -3 mA. The efficiency of the resulting solar cell system by 1,26 x 10 -2%. The results of the identification of the amount of pigment produced 8 spot with eluent ethyl acetate: formic acid: distilled water.Â Keywords: Dye sensitized solar cells, dye (dye), theaflavin